Contextualizing Contingency Management Plan: A Disaster Risk Reduction Toolkit for School Principals in the Philippines - G. Jauro, Gever; D. Siason, Nordy; G. Talaman, Suzette (International Journal of Membrane Science and Technology, 2023)
This developmental study aimed to evaluate the disaster risk reduction and management (DRRM) capabilities, preparedness, and emergency response competence of Filipino school principals in Guimaras Island, while also developing a relevant contingency management planning toolkit tailored to the needs of the region. The study involved 92 deliberately selected participants, including public elementary and secondary school principals, as well as private school administrators. Data was collected using a researcher-made questionnaire consisting of three sections: DRRM Assessment Capability, Preparedness, and Emergency Response Competence. Descriptive statistics, including frequency counts, percentage analysis, mean, standard deviation, and rank, were used for data analysis. The results indicated that both public and private school principals in Guimaras demonstrated a high capability for risk assessment, substantial preparedness, and a significant level of competence in emergency response. Notably, their assessment capability was strongest in areas such as monitoring and evaluating DRRM programs and understanding Site Development Plans, while their least predominant skills were related to maintaining and strengthening lifeline systems and estimating equipment lifespans. In terms of DRRM preparedness, strengths included utilizing DepEd Orders for class suspensions during inclement weather and providing emergency contact directories. Weaknesses were identified in areas like capacitating student-led watch teams and preparing localized school policies for disaster preparedness. Regarding emergency response, school principals were found to be highly competent in managing personnel and coordinating with the Local DRRM Team. They were also proficient in providing necessities to teachers and students and reporting damages using the RADaR App. To address the identified gaps, a contextualized toolkit was proposed, tailored to the specific needs of Guimaras schools. This toolkit received excellent ratings from experts in terms of its attributes, objectives, content, usefulness, and self-help features.